Intellectual property: the legal remedies for infringement of trade mark and common law tort of passing off (2009)
This study examines the mode of seeking redress for the infringement of trade marks both under the common law and under the statutory provision in Nigeria. In order to appreciate the economic woes inherent in unfair competitions amongst competing enterprises, the studyhighlights the nature and various types of infringements. The study also examines the effectiveness pf the statutory provisions put in place to tackle problems of unhealthy business competitions among traders. Due to the recurrent problems on the proper forum to seeking legal redress for infringement of trade marks and unfair competitions claims, the studyfurther examines the appropriate court invested with exclusive jurisdiction to adjudicate on action for infringement of trade mark in Nigeria.